Intra-industry trade in Israel: Level, explanation and implications - Richard Pomfret (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
Recent empirical studies of the phenomenon of intra-industry trade, i.e. simultaneous import and export of goods from the same industry, have found it to assume significant proportions in the industrialized countries. The present paper reports the extent of intra-industry trade in the semi-developed economy of Israel. Under the most commonly used classifications of industries, the level of intra-industry trade is found to be similar to that in the industrialized countries. An explanation of the phenomenon is sought, with particular attention being paid to the role of the aggregation procedure in determining the calculated level of intra-industry trade. The results of the paper are summarized in the final section and some implications for future research are drawn.
Keywords: 330